Application of spherical diodes for megavoltage photon beams dosimetry - Barbés, Benigno; Azcona, Juan D.; Burguete, Javier; Martí-Climent, Josep M. (Medical physics (Lancaster), 2014)
Purpose: External beam radiation therapy (EBRT) usually uses heterogeneous dose distributions in a given volume. Designing detectors for quality control of these treatments is still a developing subject. The size of the detectors should be small to enhance spatial resolution and ensure low perturbation of the beam. A high uniformity in angular response is also a very important feature in a detector, because it has to measure radiation coming from all the directions of the space. It is also convenient that detectors are inexpensive and robust, especially to performin vivo measurements. The purpose of this work is to introduce a new detector for measuring megavoltage photon beams and to assess its performance to measure relative dose in EBRT. Methods: The detector studied in this work was designed as a spherical photodiode (1.8 mm in diameter). The change in response of the spherical diodes is measured regarding the angle of incidence, cumulated irradiation, and instantaneous dose rate (or dose per pulse). Additionally, total scatter factors for large and small fields (between 1 × 1 cm2 and 20 × 20 cm2) are evaluated and compared with the results obtained from some commercially available ionization chambers and planar diodes. Additionally, the over-response to low energy scattered photons in large fields is investigated using a shielding layer. Results: The spherical diode studied in this work produces a high signal (150 nC/Gy for photons of nominal energy of 15 MV and 160 for 6 MV, after 12 kGy) and its angular dependence is lower than that of planar diodes: less than 5% between maximum and minimum in all directions, and 2% around one of the axis. It also has a moderated variation with accumulated dose (about 1.5%/kGy for 15 MV photons and 0.7%/kGy for 6 MV, after 12 kGy) and a low variation with dose per pulse (±0.4%), and its behavior is similar to commercial diodes in total scatter factor measurements. Conclusions: The measurements of relative dose using the spherical diode described in this work show its feasibility for the dosimetry of megavoltage photon beams. A particularly important feature is its good angular response in the MV range. They would be good candidates forin vivo dosimetry, and quality assurance of VMAT and tomotherapy, and other modalities with beams irradiating from multiple orientations, such as Cyberknife and ViewRay, with minor modifications.